The immunological case for staying active during the COVID-19 pandemic - Simpson, R. J.; Katsanis, E. (Brain, Behavior, and Immunity, 2020)
The COVID-19 pandemic has raised many questions regarding how we can boost immunity through exercise. There is no scientific data on how physical activity may enhance immune responses against coronaviruses, but we do know that having elevated levels of cardiorespiratory fitness and exercising at moderate to vigorous intensity can improve immune responses to vaccination, reduce chronic low-grade inflammation and improve various immune markers in several disease states including cancer, HIV, cardiovascular disease, diabetes, cognitive impairment and obesity (Duggal et al., 2019, Walsh et al., 2011).